Community resilience to flood disaster in Krajan Village, Waru District, Sidoarjo, East Java - Azzahro, Ayu Fatimah (Journal of Marine Resources and Coastal Management, 2023)
Floods that occur in Waru District often hit Krajan Village as one of the areas that is prone to flooding. Communities need to have resilience in order to be able to manage disasters well through adaptation, maintain basic functions and bounce back immediately after a disaster. Therefore, this research was conducted with the aim of analyzing the level of resilience of the Krajan Village community in facing floods.  In this research, Climate and Disaster Resilience Initiative (CDRI) was chosen as the main approach because of its suitability for application in the study area. This type of research method is quantitative with a descriptive survey research design. The population in this study were residents of Krajan Village, Waru District, as the area most affected by flooding. Data collection was carried out deliberately to 45 respondents whose houses were scattered throughout Krajan Village. Data analysis was carried out using simple tabulations and quantitative descriptives. The results showed that the people of Krajan Village, Waru District, on average, have higher resilience to flood disasters. Most of the respondents have a high level of resilience on economic dimension and have a low level of resilience on institutional dimension.